Reflection for well-being: the reflective practice experiences of social workers employed in global development. Issue 2 (4th March 2023) - Strumm, Brianna
ABSTRACT: Reflective practice is an important and influential component of social work and is often perceived as a contributing factor to professional development, experiential learning, and practice growth. However, the relationship between reflective practice and practitioner self-care, resiliency, and well-being is not commonly discussed. Furthermore, reflective practice is also not often examined within international domains of social work practice, and how practitioners who are working abroad and away from their home communities utilize reflective practice. This doctoral research project sought to explore the impact of reflective practice on workers who were practicing social work in a global development capacity. These workers crossed international borders as they practiced in foreign contexts. A meaningful discovery was how reflective practice was discussed as a conduit for self-care as practitioners worked in challenging and complex conditions that often lacked formal supervision and support. Participants spoke of how they coped with challenges by engaging in reflective practice.